2021
DOI: 10.3390/s21186199
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Divide Grouping Non-Orthogonal Multiple Access in Terrestrial-Satellite Integrated Network

Abstract: Non-orthogonal multiple access (NOMA) has been extensively studied to improve the performance of the Terrestrial-Satellite Integrated Network (TSIN) on account of the shortage of frequency band resources. In this paper, the terrestrial network and satellite network synergistically provide complete coverage for ground users, and based on the architecture, we first formulate a constrained optimization problem to maximize the sum rate of the TSIN under the limited spectrum resources. As the terrestrial networks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Step 1: calculate ϱ l,i and ϱ l,j for the given Θ while not converge do for t = 1 : t max do Compute R l,i +R l,j P l (ϱ l,i +ϱ l,j )+pc (t) Update λ 1 , λ 2 , λ 3 , λ 4 by ( 23)- (26) Compute ϱ l,i and ϱ l,j using ( 18) and ( 22 dBi, G max = 52.1 dBi, and the height of the LEO satellite is 554.8 km [47]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1: calculate ϱ l,i and ϱ l,j for the given Θ while not converge do for t = 1 : t max do Compute R l,i +R l,j P l (ϱ l,i +ϱ l,j )+pc (t) Update λ 1 , λ 2 , λ 3 , λ 4 by ( 23)- (26) Compute ϱ l,i and ϱ l,j using ( 18) and ( 22 dBi, G max = 52.1 dBi, and the height of the LEO satellite is 554.8 km [47]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al [25] have derived closed-form solutions for the achievable and asymptotic outage probability of satellite networks under hardware impairment and imperfect signal decoding. Moreover, the authors of [26] have proposed a joint power and channel allocation framework to maximize the sum rate of terrestrial-satellite networks. The research work in [27] has provided a fair resource allocation framework in cooperative satellite networks to maximize the minimum capacity.…”
Section: A Recent Literature On Leo Satellite Networkmentioning
confidence: 99%
“…Strategically utilizing UP schemes aims to enhance spectral efficiency, improve throughput, and manage interference, thereby optimizing the overall performance of aerial communication networks. The work of [61] suggested that a distance-based model can be utilized to establish NOMA-UP with stable channel differences.…”
Section: User-pairingmentioning
confidence: 99%
“…In cellular mobile communications, the design of the radio access network (RAN) is one important aspect of improving system capacity in a cost-effective manner. Orthogonal multiaccess (OMA) techniques, under the name of orthogonal frequency division multiple access (OFDMA), are used in the Fourth Generation (4G) long-term evolution (LTE) [7][8][9][10]. In OMA, within a cell, each user has exclusive access to the allocated resource blocks.…”
Section: Introductionmentioning
confidence: 99%